ChemInform Abstract: A New Indole Alkaloid from Voacanga grandifolia. Issue 21 (May 2015) - Morita, Hiroshi; Haseo, Azusa; Eko Nugroho, Alfarius; Hirasawa, Yusuke; Kaneda, Toshio; Shirota, Osamu; Rahman, Abdul; Kusumawati, Idha; Cholies Zaini, Noor
Abstract isolation and structure elucidation of the new vobasine‐iboga type bisindole alkaloid, voacalgine F (I)